Drought enhances folivory by shifting foliar metabolomes in Quercus ilex trees. - Rivas-Ubach, Albert; Gargallo-Garriga, Albert; Sardans, Jordi; Oravec, Michal; Mateu-Castell, Laia; Pérez-Trujillo, Míriam; Parella, Teodor; Ogaya, Romà; Urban, Otmar; Penuelas, Josep (The New phytologist, 2014)
At the molecular level, folivory activity on plants has mainly been related to the foliar concentrations of nitrogen (N) and/or particular metabolites. We studied the responses of different nutrients and the whole metabolome of Quercus ilex to seasonal changes and to moderate field experimental conditions of drought, and how this drought may affect folivory activity, using stoichiometric and metabolomic techniques. Foliar potassium (K) concentrations increased in summer and consequently led to higher foliar K : phosphorus (P) and lower carbon (C) : K and N : K ratios. Foliar N : P ratios were not lowest in spring as expected by the growth rate hypothesis. Trees exposed to moderate drought presented higher concentrations of total sugars and phenolics and these trees also experienced more severe folivory attack. The foliar increases in K, sugars and antioxidant concentrations in summer, the driest Mediterranean season, indicated enhanced osmoprotection under natural drought conditions. Trees under moderate drought also presented higher concentrations of sugars and phenolics; a plant response to avoid water loss. These shifts in metabolism produced an indirect relationship between increased drought and folivory activity.
Keywords: Drought; ecology; ecometabolomics; folivory; metabolomics

Foliar CO2 in a holm oak forest subjected to 15 years of climate change simulation - Ogaya, Romà; Llusia, Joan; Barbeta, Adrià; Asensio, Dolores; Liu, Daijun; Alessio, Giorgio Arturo; Penuelas, Josep (Plant Science, 2014)
A long-term experimental drought to simulate future expected climatic conditions for Mediterranean forests, a 15% decrease in soil moisture for the following decades, was conducted in a holm oak forest since 1999. Net photosynthetic rate, stomatal conductance and leaf water potential were measured from 1999 to 2013 in Quercus ilex and Phillyrea latifolia, two co-dominant species of this forest. These measurements were performed in four plots, two of them received the drought treatment and the two other plots were control plots. The three studied variables decreased with increases in VPD and decreases in soil moisture in both species, but the decrease of leaf water potential during summer drought was larger in P. latifolia, whereas Q. ilex reached higher net photosynthetic rates and stomatal conductance values during rainy periods than P. latifolia. The drought treatment decreased ca. 8% the net photosynthetic rates during the overall studied period in both Q. ilex and P. latifolia, whereas there were just non-significant trends toward a decrease in leaf water potential and stomatal conductance induced by drought treatment. Future drier climate may lead to a decrease in the carbon balance of Mediterranean species, and some shrub species well resistant to drought could gain competitive advantage relative to Q. ilex, currently the dominant species of this forest.
Keywords: climate change; Drought; mediterranean forest; phillyrea latifolia; photosynthetic rates; Quercus ilex

Dampening effects of long-term experimental drought on growth and mortality rates of a Holm oak forest - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (GLOBAL CHANGE BIOLOGY, 2013)
Forests respond to increasing intensities and frequencies of drought by reducing growth and with higher tree mortality rates. Little is known, however, about the long-term consequences of generally drier conditions and more frequent extreme droughts. A Holm oak forest was exposed to experimental rainfall manipulation for 13years to study the effect of increasing drought on growth and mortality of the dominant species Quercus ilex, Phillyrea latifolia, and Arbutus unedo. The drought treatment reduced stem growth of A. unedo (-66.5%) and Q. ilex (-17.5%), whereas P. latifolia remained unaffected. Higher stem mortality rates were noticeable in Q. ilex (+42.3%), but not in the other two species. Stem growth was a function of the drought index of early spring in the three species. Stem mortality rates depended on the drought index of winter and spring for Q. ilex and in spring and summer for P. latifolia, but showed no relation to climate in A. unedo. Following a long and intense drought (2005-2006), stem growth of Q. ilex and P. latifolia increased, whereas it decreased in A. unedo. Q. ilex also enhanced its survival after this period. Furthermore, the effect of drought treatment on stem growth in Q. ilex and A. unedo was attenuated as the study progressed. These results highlight the different vulnerabilities of Mediterranean species to more frequent and intense droughts, which may lead to partial species substitution and changes in forest structure and thus in carbon uptake. The response to drought, however, changed over time. Decreased intra- and interspecific competition after extreme events with high mortality, together with probable morphological and physiological acclimation to drought during the study period, may, at least in the short term, buffer forests against drier conditions. The long-term effects of drought consequently deserve more attention, because the ecosystemic responses are unlikely to be stable over time.Nontechnical summaryIn this study, we evaluate the effect of long-term (13years) experimental drought on growth and mortality rates of three forest Mediterranean species, and their response to the different intensities and durations of natural drought. We provide evidence for species-specific responses to drought, what may eventually lead to a partial community shift favoring the more drought-resistant species. However, we also report a dampening of the treatment effect on the two drought-sensitive species, which may indicate a potential adaptation to drier conditions at the ecosystem or population level. These results are thus relevant to account for the stabilizing processes that would alter the initial response of ecosystem to drought through changes in plant physiology, morphology, and demography compensation.
Keywords: acclimation; Arbutus unedo; experimental drought; global-change-type drought; Holm oak; mediterranean forest; phillyrea latifolia; Quercus ilex; tree growth; tree mortality; vegetation stabilizing processes

Disparity in elevational shifts of European trees in response to recent climate warming - Rabasa, Sonia G; Granda, Elena; Benavides, Raquel; Kunstler, Georges; Espelta, Josep M; Ogaya, Romà; Penuelas, Josep; Scherer-Lorenzen, Michael; Gil, Wojciech; Grodzki, Wojciech; Ambrozy, Slawomir; Bergh, Johan; et al. (GLOBAL CHANGE BIOLOGY, 2013)
Predicting climate-driven changes in plant distribution is crucial for biodiversity conservation and management under recent climate change. Climate warming is expected to induce movement of species upslope and towards higher latitudes. However, the mechanisms and physiological processes behind the altitudinal and latitudinal distribution range of a tree species are complex and depend on each tree species features and vary over ontogenetic stages. We investigated the altitudinal distribution differences between juvenile and adult individuals of seven major European tree species along elevational transects covering a wide latitudinal range from southern Spain (37 degrees N) to northern Sweden (67 degrees N). By comparing juvenile and adult distributions (shifts on the optimum position and the range limits) we assessed the response of species to present climate conditions in relation to previous conditions that prevailed when adults were established. Mean temperature increased by 0.86 degrees C on average at our sites during the last decade compared with previous 30-year period. Only one of the species studied, Abies alba, matched the expected predictions under the observed warming, with a maximum abundance of juveniles at higher altitudes than adults. Three species, Fagus sylvatica, Picea abies and Pinus sylvestris, showed an opposite pattern while for other three species, such as Quercus ilex, Acer pseudoplatanus and Q. petraea, we were no able to detect changes in distribution. These findings are in contrast with theoretical predictions and show that tree responses to climate change are complex and are obscured not only by other environmental factors but also by internal processes related to ontogeny and demography.
Keywords: altitudinal gradient; climate change; FOREST; generalized additive models; Species distribution

Field-simulated droughts affect elemental leaf stoichiometry in Mediterranean forests and shrublands - Sardans, Jordi; Rivas-Ubach, Albert; Estiarte, Marc; Ogaya, Romà; Penuelas, Josep (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2013)
This study evaluated the change induced by the year season and by experimentally induced drought on foliar element stoichiometry of the predominant woody species (Quercus ilex and Erica multiflora) in two Mediterranean ecosystems, a forest and a shrubland. This study is based in two long-term (11 yr) field experiments that simulated drought throughout the annual cycle. The effects of experimental droughts were significant but weaker than the changes produced by ontogeny and seasonality. Leaf N and P concentrations were higher in spring (the main growing season) in E. multiflora and, in Q. ilex in autumn (a period of additional growth). Leaf N:P ratios were lower in spring. In Q. ilex, the highest leaf K concentrations and leaf K:P ratios, and the lowest leaf C:K and N:K ratios, occurred in summer, the season when water stress was greatest. In E. multiflora, leaf K concentrations and K:P ratios were highest, and leaf C:K and N:K ratios were lowest in the plants from the drought-treated plots. The plant capacity to change K concentrations in response to seasonality and to drought is at least as great as the capacity to change N and P concentrations. The results underscore the importance of K and its stoichiometry relative to C, N and P in dry environments. These results indicate first, that N:P ratio shifts are not uniquely related to growth rate in Mediterranean plants but also to drought, and second, that there is a need to take into account K in ecological stoichiometry studies of terrestrial plants. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: climate change; Drought; Growth rate hypothesis; N:P; nitrogen; Ontogeny; phosphorus; Potassium

Comparative study of diurnal and nocturnal sap flow of Quercus ilex and Phillyrea latifolia in a Mediterranean holm oak forest in Prades (Catalonia, NE Spain) - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (Trees, 2012)
Droughts are a cyclical disturbance in Mediterranean ecosystems and climate change models forecast an increase of their frequency and severity. Some experimental and observational studies have shown that cooccurring species may cope with drier conditions with different strategies and present different responses. Here, we investigate sap ﬂow response to drought in order to explain the observed differential growth and mortality of Quercus ilex and Phillyrea latifolia at Prades Holm oak forest (NE Spain). We measured sap ﬂow of these species and compared their diurnal, nocturnal and seasonal patterns and their relationship with environmental variables. Both species described qualitatively similar daily patterns, either during daylight or night. Sap ﬂow rates were signiﬁcantly higher in P. latifolia except in autumn and spring. P. latifolia was more sensitive to soil moisture. Nocturnal sap ﬂow was detected in both species with no signiﬁcant differences and hourly rates suffered a progressive increase from 3 a.m. to dawn in most sampled nights. Our results indicate a better adaptation of P. latifolia to this site as it can take better advantage of wet periods while maintaining higher sap ﬂow rates during dry periods. Along with previous ecophysiological studies at the same location it may be inferred that at its drier distributional limit Q. ilex would be at disadvantage with respect to other species like P. latifolia, as the latter would cope better with increasing xeric conditions already occurring and further predicted for Mediterranean ecosystems. Our results also show nocturnal sap ﬂow to be relevant in individual water losses in these two species as they can be up to 35–40 % of daily sap ﬂow. Further research on the underlying mechanisms of this nocturnal sap ﬂow is required since it may also enhance early morning CO2 ﬁxation or nutrient supply to leaves.
Keywords: á; Drought; ilex á sap flow; nocturnal sap flow; nocturnal sap flow á; phillyrea latifolia; phillyrea latifolia á quercus; Quercus ilex; sap flow

Leaf and stand-level carbon uptake of a Mediterranean forest estimated using the satellite-derived reflectance indices EVI and PRI - Garbulsky, Martín F.; Penuelas, Josep; Ogaya, Romà; Filella, Iolanda (International Journal of Remote Sensing, 2012)
Various aspects of global environmental change affect plant photosynthesis, the primary carbon input in ecosystems. Thus, accurate methods of measuring plant photosynthesis are important. Remotely sensed spectral indices can monitor in detail the green biomass of ecosystems, which provides a measure of potential photosynthetic capacity. In evergreen vegetation types, however, such as Mediterranean forests, the amount of green biomass changes little during the growing season and, therefore, changes in green biomass are not responsible for changes in photosynthetic rates in those forests. This study examined the net photosynthetic rates and the diametric increment of stems in a Mediterranean forest dominated by Quercus ilex using three spectral indices (normalized difference vegetation index (NDVI), enhanced vegetation index (EVI), and photochemical reflectance index (PRI)) derived from Moderate Resolution Imaging Spectroradiometer (MODIS) sensors. Average annual EVI accounted for 83% of the variability of the diametric increment of Q. ilex stems over a 10 year period. NDVI was marginally correlated with the diametric increment of stems. This study was the first to identify a significant correlation between net photosynthetic rates and radiation use efficiency at the leaf level using PRI derived from satellite data analysed at the ecosystem level. These results suggest that each spectral index provided different and complementary information about ecosystem carbon uptake in a Mediterranean Q. ilex forest.
doi: 10.1080/01431161.2012.718457doi: 10.1080/01431161.2012.718457The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: carbon uptake (voyant); EVI; mediterranean forest; NDVI; photochemical reflectance index (PRI)

Chlorophyll fluorescence responses to temperature and water availability in two co-dominant Mediterranean shrub and tree species in a long-term field experiment simulating climate change - Ogaya, Romà; Penuelas, Josep; Asensio, Dolores; Llusia, Joan (Environmental and Experimental Botany, 2011)
A rain exclusion experiment simulating drought conditions expected in Mediterranean areas for the following decades (15% decrease in soil moisture) is being conducted since 1999 in a Mediterranean holm oak forest to study its response to the forecasted climatic changes for the coming decades. The maximum PSII quantum yield of primary photochemistry (Fv/Fm) was measured in Quercus ilex, and Phillyrea latifolia, the co-dominant species of the studied forest, from 1999 to 2009 in four plots: two of them were control plots and the other two plots received the rain exclusion treatment. In both species, the Fv/Fm values were highly dependent on air temperatures, and in a second term, in water availability. P. latifolia was the species with the larger decrease in Fv/Fm values induced by low air temperatures, while in hot seasons, the Fv/Fm values in P. latifolia were even higher than in Q. ilex. Rainfall exclusion decrease Fv/Fm values signiﬁcantly only in few monitoring dates. The most drought resistant species P. latifolia was more affected by the experimental rainfall exclusion than Q. ilex that instead lost number of leaves per tree. There was a synergic effect of drought stress and winter cold in P. latifolia not observed in Q. ilex, but a more conservative strategy in P. latifolia maintaining leaves with a down-regulation of the linear photosynthetic electron transport. These results indicate that, although other physiological and reproductive strategies at whole plant level must be also taken into account, the warmer and drier environment expected for the following decades could favour the species more sensitive to cold and more resistant to drought, the shrub P. latifolia, in detriment of the tree Q. ilex as already observed in the ﬁeld after severe heat-drought episodes.
Keywords: Chlorophyll ﬂuorescence; climate change; Cold; Drought; evergreen leaves; Fv/Fm; Heat; mediterranean forest; phillyrea latifolia; Quercus ilex

Migration, invasion and decline: changes in recruitment and forest structure in a warming-linked shift of European beech forest in Catalonia (NE Spain) - Penuelas, Josep; Ogaya, Romà; Boada, Martí; Jump, Alistair S. (ECOGRAPHY, 2007)
Altitudinal upward shifts of species' ranges have occurred across a wide range of taxonomic groups and geographical locations during the twentieth century in response to current climate warming. However, actual data of plant species' altitudinal shifts are still scarce and not always clear. Here we provide a more detailed investigation of a previously reported European beech Fagus sylvatica forest altitudinal shift in the Montseny Mountains (Catalonia, NE Spain) now based on field photographic survey and on the population age structure and the recruitment patterns in the high Fagus limit (HFL), the central forest area (CFA) and the low Fagus limit (LFL). Monitoring of the lowest altitudinal range shows that beech forest is being progressively replaced by Mediterranean holm oak forest. Holm oaks are characterized by recruitment rates more than three times higher than those of beech in the LFL in the last decades. The percentage of young individuals in the LFL is only half that in the HFL and CFA. In the highest altitudinal range, present day and early 20th century photographs show that the HFL has gained density and has shifted altitudinally upwards, advancing with establishment of new, vigorous outpost trees (13 individuals per each 100 m of tree-line). They are mostly (89%) younger than 35 yr old and mostly (97%) located up to 70 m (with a few up to 105 m) ground surface distance above the current tree line (36-51 m altitude) at the highest altitudes (1600-1700 m). The beech forest upward shift is a likely consequence of warming, but land-use practice changes (cessation of burning by shepherds) have made it possible. These changes in vegetation distribution and population structure constitute a new indication of the complex global change effects on life in mountain ecosystems.
APSAPSThe following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: altitudinal shifts; climate warming; geographical locations; species ranges; taxonomic groups

Migration, invasion and decline: changes in recruitment and forest structure in a warming-linked shift of European beech forest in Catalonia (NE Spain) - Penuelas, Josep; Ogaya, Romà; Boada, Martí; Jump, Alistair S (ECOGRAPHY, 2007)
Altitudinal upward shifts of species' ranges have occurred across a wide range of taxonomic groups and geographical locations during the twentieth century in response to current climate warming. However, actual data of plant species' altitudinal shifts are still scarce and not always clear. Here we provide a more detailed investigation of a previously reported European beech Fagus sylvatica forest altitudinal shift in the Montseny Mountains (Catalonia, NE Spain) now based on field photographic survey and on the population age structure and the recruitment patterns in the high Fagus limit (HFL), the central forest area (CFA) and the low Fagus limit (LFL). Monitoring of the lowest altitudinal range shows that beech forest is being progressively replaced by Mediterranean holm oak forest. Holm oaks are characterized by recruitment rates more than three times higher than those of beech in the LFL in the last decades. The percentage of young individuals in the LFL is only half that in the HFL and CFA. In the highest altitudinal range, present day and early 20th century photographs show that the HFL has gained density and has shifted altitudinally upwards, advancing with establishment of new, vigorous outpost trees (13 individuals per each 100 m of tree-line). They are mostly (89%) younger than 35 yr old and mostly (97%) located up to 70 m (with a few up to 105 m) ground surface distance above the current tree line (36-51 m altitude) at the highest altitudes (1600-1700 m). The beech forest upward shift is a likely consequence of warming, but land-use practice changes (cessation of burning by shepherds) have made it possible. These changes in vegetation distribution and population structure constitute a new indication of the complex global change effects on life in mountain ecosystems.
APS
Keywords: altitudinal shifts; climate warming; geographical locations; species ranges; taxonomic groups

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Establishment of co-existing Mediterranean tree species under a varying soil moisture regime - Lloret, Francisco; Penuelas, Josep; Ogaya, Romà (Journal of Vegetation Science, 2004)
We investigated the responses of two co-existing Mediterranean trees with different regeneration strategies (Phillyrea latifolia seedlings and Quercus ilex sprouts) to experimental drought below the forest canopy. We considered different recruitment stages and used leaf isotopic discrimination to estimate water use efficiency (WUE) and nitrogen availability and use. Drought decreased the emergence and survival of seedlings and sprouts. Survival and growth of older saplings were not influenced by drought. Seedling emergence of P. latifolia was higher than Q. ilex sprout production, but Q. ilex sprouts had higher survival and growth rates. These differences disappeared in the sapling stage. Carbon isotopic discrimination suggested that Q. ilex sprouts had higher WUE than P. latifolia seedlings. Drought increased WUE of recruits, particularly in Q. ilex. Water use regulation increased with ageing, particularly in P. latifolia. Q. ilex had higher δ15N values than P. latifolia; these were also higher under drier soil conditions. Current year seedlings had higher δ15N than saplings, particularly in P. latifolia, suggesting they exploit superficial soil layers. These results suggest that sprouts obtain benefit from resources stored in parent plants. At earlier stages, they perform better than seedlings. This response is not coupled to adult vulnerability to drought for these species, revealing the difficulty of predicting species dynamics during climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate change; Drought; mediterranean forest; Nitrogen use; phillyrea latifolia; Quercus ilex; Recruitment; Regeneration; Seedling; sprouting; water use efficiency